Rotating helical turbulence. II. Intermittencyscale invarianceand structures - Mininni, P.D. (2010)
We study the intermittency properties of the energy and helicity cascades in two 15363 direct numerical simulations of helical rotating turbulence. Symmetric and antisymmetric velocity increments are examinedas well as probability density functions of the velocity field and of the helicity density. It is found that the direct cascade of energy to small scales is scale invariant and nonintermittentwhereas the direct cascade of helicity is highly intermittent. Furthermorethe study of structure functions of different orders allows us to identify a recovery of isotropy of strong events at very small scales in the flow. Finallywe observe the juxtaposition in space of strong laminar and persistent helical columns next to time-varying vortex tanglesthe former being associated with the self-similarity of energy and the latter with the intermittency of helicity. © 2010 American Institute of Physics.